Aripiprazole Toxicity With a Biphasic Course of Somnolence. Issue 8 (August 2019) - Gupta, Divya; O'Hara, Chris
Abstract : Introduction: Aripiprazole is an atypical antipsychotic with partial agonism at dopamine and serotonin receptors. In pediatrics, it is approved to treat irritability associated with autistic disorder along with other neuropsychological conditions. Compared with other atypical antipsychotics, it has a favorable side effect profile, but overdose experience is limited. Case Report: A 3-year-old drug-naive patient accidentally ingested 200 mg of aripiprazole. This ingestion resulted in immediate lethargy with brief improvement 16 hours after ingestion and subsequent decline 2 hours later. Patient returned to baseline 72 hours after ingestion. Discussion: Unlike previous case reports, this patient displayed a biphasic course of somnolence. Previous reports have described delayed onset and prolonged sedation in response to an aripiprazole overdose. Current recommendations regarding monitoring after ingestion do not account for possible worsening of symptoms after improvement. Conclusion: It is important to recognize the need for a longer observation period after a significant aripiprazole overdose as a variable course of somnolence may be witnessed.